Diseases Pattern in the Department of Physical Medicine & Rehabilitation in a Tertiary Level Hospital - Amin, Md Ruhul; Parvin, Sanjida; Kabir, Jesmin (Chest & Heart Journal, 2021)
This is a retrospective study carried out at the department of Physical Medicine and Rehabilitation in National Institute of Diseases of the Chest and Hospital (NIDCH), Dhaka for the period of one year from 1st July, 2019 to 30thJune, 2020. The purpose of the study was to observe the disease pattern and demographic characteristics of patients attending the department of Physical Medicine and Rehabilitation in a tertiary care hospital. Total one thousand three hundred and fifty two (n=1352) patients were studied, of which 938(69%) were male and 414(31%) were female. Maximum patients 329(23.90%) belong to above 60 years of age. Maximum patients 973(72%) were come from outside Dhaka city and most of the studied patients were farmers 392(29%). Largest disease group was COPD 202(14.94%). Regarding disease pattern, 913(67.52%) of patientspulmonary problem and rest 439(32.48%) were non pulmonary problem. Among leading diseases, 202(14.94%) were COPD, 182(13.46%) pulmonary fibrosis, 175(12.94%) bronchiectasis, 107(7.91%) lung abscess, 131(9.69%) postsurgical, 116(8.58%) asthma , 126(9.39%) adhesive capsulitis, 119(8.8%) cervical spondylosis, 116(8.58%) low back pain, 77(5.69%) others. Chest Heart J. 2020; 44(2) : 96-99